2016
DOI: 10.1016/j.cognition.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Young children’s preference for unique owned objects

Abstract: An important aspect of human thought is the value we place on unique individuals. Adults place higher value on authentic works of art than exact replicas, and young children at times value their original possessions over exact duplicates. What is the scope of this preference in early childhood, and when do children understand its subjective nature? On a series of trials, we asked three-year-olds (N=36) to choose between two toys for either themselves or the researcher: an old (visibly used) toy versus a new (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 59 publications
1
43
0
1
Order By: Relevance
“…year-olds prefer their old stuffed animals and sleep items over new replacements, but do not have this preference with regular toys (Gelman & Davidson, 2016). Also, adults' valuations of an object are enhanced if the object is presented with a historical narrative (e.g., detailing how it was obtained or created); however, this effect is greater for objects that resemble living things than for other objects (Newman, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…year-olds prefer their old stuffed animals and sleep items over new replacements, but do not have this preference with regular toys (Gelman & Davidson, 2016). Also, adults' valuations of an object are enhanced if the object is presented with a historical narrative (e.g., detailing how it was obtained or created); however, this effect is greater for objects that resemble living things than for other objects (Newman, 2018).…”
Section: Resultsmentioning
confidence: 94%
“…Children may predominantly respect others' ownership rights, but may have limited awareness that they prefer their own belonging over other objects. It is especially likely that children may lack awareness that ownership affects their preferences given that these effects may be fragile for most objects (Gelman et al, 2012;Harbaugh, Krause, & Vesterlund, 2001;Hood et al, 2016;Lucas et al, 2008), and only robust for stuffed animals and sleep-objects (Gelman & Davidson, 2016). As such, it might be interesting to explore whether children would be more likely to appreciate that others will prefer their belongings over other items if asked about such objects.…”
Section: Discussionmentioning
confidence: 99%
“…Some experiments have found that preschoolers and young children come to prefer objects that were recently assigned to them (Gelman, Manczak, & Noles, 2012;Harbaugh, Krause, & Vesterlund, 2001), though these effects may be fragile (Hood, Weltzien, Marsh, & Kanngiesser, 2016;Lucas, Wagner, & Chow, 2008; also see Hood & Bloom, 2008). However, dramatic evidence that ownership is linked with inflated preferences comes from findings showing that 3year-olds prefer their own visibly-used toys over new replacements (Gelman & Davidson, 2016).…”
Section: Inferring Preferencesmentioning
confidence: 99%
“…Neutralization of these contaminated items by families and caregivers may be a simple and effective part of the effort to prevent SSI by decreasing the overall bacterial load within the sterile environment of the operating suite. Parents' and doctors' visual evaluation of teddy bear cleanliness and fluffiness may lead to the suggestion that children and families bring a new, clean teddy bear for planned surgeries; however, as demonstrated by Gelman et al [27] in a study of thirty-six 3-year-old children, children prefer their original, worn toy over a new replica.…”
Section: Discussionmentioning
confidence: 99%